Tooth Root Bending Fatigue Performance of Shot Peening TM210A Steel Spur Gear - H. J. Xu; Guang-Qiang Yin; X. Y. Tong; S. L. Lv (Advances in Materials Science and Engineering)
Tooth root bending fatigue performance is the primary consideration in gear design. To investigate the difference between the tooth root fatigue performances of shot peened and base material, TM210A steel gears and double-tooth pulsating bending fatigue experiment with a stress ratio of 0.05 was carried out on the experimental gears by the group method and the staircase method. The fatigue life of experimental gears with different stress levels and the conditional fatigue limit under 1 × 107 cycles were obtained, and the S-N curves were fitted by the double-weighted least squares method. The tooth root residual stress of the shot peened gear was measured by the X-ray diffraction method, the stress field at the tooth root was calculated by the finite element method, and the fatigue failure mechanism of the shot peened gear tooth root was analyzed. The results show that shot peening can significantly enhance the tooth root bending fatigue life and strength of TM210A steel gear, and the tooth root bending fatigue limit of shot peened gear is about 2.18 times that of base material gear. The residual stress generated by shot peening keeps the fatigue source away from the tooth root surface, and the smaller the external load stress, the farther the fatigue source is from the surface, and the smaller the range where the fatigue source can occur.